New records of water striders (Hemiptera: Heteroptera: Gerridae) from Nicaragua and additional records for Costa Rica - Herrera, Federico (2014)
The presence in Nicaragua of the species Trepobates taylori, Trepobates trepidus and Limnogonus franciscanus, not previously-reported for the country, is confirmed. Besides, other distributional records of the genera Trepobates and Limnogonus are provided for Costa Rica.